Learning with ICT: development of young learners' writing skills - Mat Daud, Nuraihan (2010)
Abstract: This paper discusses the ICT facilities used by young learners to develop their language proficiency. A longitudinal study (four years) on one nine year old child shows that power-point alone provided an interesting tool for a child to develop various aspects of writing. The bigger children preferred sites which were more interactive. The real audience made these sites a suitable medium for developing their communication skills. The study shows that the learners improved in their writing skills with time and the Internet was a suitable tool for developing their communication skills. The analysis also reflects that the relationship between having a computer at home and access to the Internet, and students’ performance in the English language at school was statistically significant.